Draft Five Year Plan 1978-83 Arunachal Pradesh - Planning Commission (Planning Commission, 1978)
Larger stress on production of commercial and cash crop like Potato, Mustard, Soya beans, Ginger, Mung, Chillies, Black pepper, (11 seeds, cotton are being given to maintain the thrust towards increasing the employment intensity and benefiting the poor people struggling below the poverty line. A modest beginning was made during Fifth Five Year Plan by bringing 3004 hect. of land under such cultivation. By the end of five year plan 1973-83 an area of 9440 hect. is proposed to be brought under such cultivation.
Government of Arunachal Pradesh Planning and Development Department
Government of Arunachal Pradesh Planning and Development Department